The Meaning of Media : Texts and Materiality in Medieval Scandinavia. - Horn, Anna Catharina. (Modes of Modification Series, 2021)
Variance characterises the textual culture of the Middle Ages on all levels. Analysing this variance is paramount to understand the norms and transformations involved in the process of establishing a literate culture. This series focuses on the literate output in the Nordic region, from the perspective of Modes of Modification. In order to place the region in a larger context, it also encourages comparative studies with a wider European view.